A walk in her shoes [videorecording (DVD)] : an homage to the life and legacy of Harriet Tubman - Garcia, Selina; Lundy, Metra; Lundy, Metra (IndiePix, 2021)
Revolves around a woman, who decided to undertake the same 695 mile journey that Harriet Tubman walked in the 1800s to free herself and others from slavery.